Competition for traders and risk. (26th September 2018) - Bijlsma, Michiel; Boone, Jan; Zwart, Gijsbert
Abstract: Perverse incentives for banks' traders have played a role in the financial crisis. We study how labor market competition interacts with the structure of compensation to result in excessive risk taking. In a model with trader moral hazard and adverse selection on trader abilities, we demonstrate how banks optimally induce top traders to take more risk as competition on the labor market intensifies, even if banks internalize the costs of negative outcomes. Distorting risk‐taking incentives allows banks to reduce the surplus offered to low‐ability traders. We find that increasing bank capital requirements does not unambiguously reduce risk taking by top traders.